The systematization of Gaius in the secular and canonical collections of law - Sacher, Andrzej (Prawo Kanoniczne, 2021)
The article entitled The systematization of Gaius in the secular and canonical collections of law focuses primarily on the author of the Roman law textbook written in the 2nd century AD and, further, brings to light the characteristics of the work. The arrangement of the legal material as regards the Institutes of Gaius is referred to as the personae – res – actiones division. The author of the article emphasizes the role that the systematics of Gaius played in the creation of collections of law and canon law. The Justinian Code, as analyzed in the article, and the modern civil codes based on its systematization became the reference point for the shape of the first Code of Canon Law promulgated in 1917